Kemampuan Mengelola Modal Kerja Para Pengusaha Kecil di Wilayah Bogor Barat - Nina Agustina (STIE Binaniaga, 2007)
Crisis condition in Indonesia since the middle 1997 has show us many firm had collapse, but, many small firms can survive although they did not have access to bank, to have some aid for their business. The purpose of this study is to find out, how the small business managed their working capital, so, if they have aid some credit from the bank, they can paid back their credit. And, it’s mean, they can improve their productivity.